Sustainability and Social Responsibility of Accountability Reporting Systems A Global Approach (Accounting, Finance, Sustainability, Governance & Fraud: Theory and Application,, 2018)
This book explores sustainability and social responsibility from the point of view of accountability reporting systems. The contributions to this volume open up discussions about the theory and application of sustainability and social responsibility across various corporate sectors and assists the reader in applying sustainable corporate social responsibility reporting across those sectors. As a central theme, the book addresses how the theory and application in sustainability and social responsibility has different dimensions and aspects which are impossible to apply across different sectors. This point of view is supported by chapter contributions from countries around the world including Turkey, Serbia, Malaysia, United States, South Africa, Italy, China, Brasil, Romania, Serbia, Puerta Rico, Algeria. Academics worldwide will discover in Sustainability and Social Responsibility of Accountability Reporting Systems: A Global Approach the latest developments about corporate social responsibility and sustainability of accountability reporting systems.